Optimalisasi Kegiatan Ekstrakurikuler Dalam Mengembangkan Soft Skills Peserta Didik - Fitriany, Sonia (Yayasan Sembilan Pemuda Indonesia, 2025)
This research aims to examine the optimization of extracurricular activities in developing students’ soft skills at SMK Setia Darma 2 Palembang. This research is a qualitative method with a case study. Data collection was carried out through observation, interviews and documentation of students, teachers and extracurricular instructors. The research results show that extracurricular activities have great potential in developing students’ soft skills, especially through activities such as scouts, OSIS organizations, and basketball club. However, optimization has not been optimal due to limited facilities, lack of supervision, and low active participation of students in these activities. The contribution of this research is improving the quality and variety of extracurricular activities, increasing teacher involvement as teachers, and supporting adequate facilities to support the development of students’ soft skills. This optimization is expected to maximize the role of extracurricular activities in shaping the character of students who are ready to compete in the world of work and able to adapt to dynamic social life.